Asymptotic analysis of a multiserver retrial queue with disasters in the service block - Meloshnikova, Natalya (Information Technologies and Mathematical Modelling. Queueing Theory and Applications : 21st International Conference, ITMM 2022, Karshi, Uzbekistan, October 25-29, 2022 : revised selected papers)
The paper studies a multiserver retrial queuing system with negative calls. The arrival processes of “positive” and “negative” calls are Poisson. Positive call’s service time is exponential distributed. Unserved calls go to an orbit, where they wait for random time distributed exponentially. Then they turn up to the service block according to the random multiple access protocol. Disasters are caused by negative calls arrivals. When a negative call comes, it resets all servers. All servicing positive calls leave the system. In the paper, a stationary probability distribution of the number of calls in orbit is found by the method of asymptotic analysis under the condition of a long delay. The results of the numerical analysis are presented.